2015
DOI: 10.1016/j.injury.2014.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and meeting information needs following unintentional injury: Comparing the accounts of patients, carers and service providers

Abstract: Abstract:OBJECTIVE: To explore information needs of unintentional injury patients and their carers over time, across services, and how such needs are met from the perspectives of patients, carers and service providers.METHODS: Qualitative nested study within a multi-centre longitudinal study quantifying psychosocial, physical, occupational outcomes and service use and costs following a range of unintentional injuries. Semi-structured interviews conducted with 45 patients during the first year post injury, 18 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 20 publications
7
39
0
Order By: Relevance
“…15 Patient and SP sampling is described in full elsewhere. 9,10 Patient interview schedules explored experiences of care post-injury while SP interviews explored experiences of providing care and individual and organisational barriers to better provision. Patient interviews were undertaken in the participant's home or by telephone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Patient and SP sampling is described in full elsewhere. 9,10 Patient interview schedules explored experiences of care post-injury while SP interviews explored experiences of providing care and individual and organisational barriers to better provision. Patient interviews were undertaken in the participant's home or by telephone.…”
Section: Resultsmentioning
confidence: 99%
“…8 Discharge home after an injury can be a difficult time and many patients report feeling inadequately prepared. 9 Contributory factors are: poorly coordinated or long waiting times for care, 10 inadequate pain control, 8,11 psychological problems, 12-14 lack of access to services, 10,11 and significant gaps in information provision. 9 Post-injury, most working-age adults consult a GP in the first month and over a third consult between 1 and 4 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health professionals routinely treating people with unintentional injuries are not mental health experts. It would be useful if they can identify patients at risk of poor recovery using standard self-report measures of psychological health and pain, help patients manage these conditions and refer to appropriate services as necessary [50, 51]. In addition, our study shows a simple and routinely available measure, such as the number of nights in hospital, can highlight those at risk of poor recovery.…”
Section: Discussionmentioning
confidence: 99%
“…They need help understanding what has happened and their projected recovery, adequate symptom control, and a joined up health care system supporting timely access to rehabilitation. Although budget restraints or provision of services may affect local access to therapies, simply meeting regularly with patients soon after the injury, providing detailed verbal and written information and reassurance, 6 and suggesting practical solutions and strategies on how to cope with symptoms or a gradual return to work can help reduce psychological distress and promote recovery. 7 Ponsford et al demonstrated that giving patients who had sustained a minor head injury an information booklet 1 week post injury resulted in significantly lower rates of stress at 3 months than those who did not receive the booklet.…”
Section: Short and Long Term Needs Of Patients Post Injurymentioning
confidence: 99%